Festival Indonesia: Answer to Indonesian Public Diplomacy Towards Russian Citizens - Achmad Ismail; Darynaufal Mulyaman; Rendy Sarudin (Parahyangan Center for International Studies, 2022)
As the Asia Rising phenomenon becomes more evident, Russia needs to look again to Asia for growth and strategic cooperation through the Far East Policy. Apart from traditional Far Eastern countries such as China, Japan, and South Korea, Indonesia as one of the Asian countries recently with a prominent future also does not waste Russia's market and strategic location that issued the policy. Indonesia respectfully maintains good relations with Russia to get more benefits and economic possibilities such as from the tourism sector. The Indonesian Festival is one of the instruments imposed and utilized by the Indonesian government to achieve the nation's economic interests. This article aims to explain that the